2004
DOI: 10.1007/s00134-003-2136-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of acute lung injury in European intensive care units

Abstract: Intensive Care Med (2003) 30:51-61 Due to an unfortunate error the second sentence in the second paragraph of "Discussion/Occurrence of acute lung injury and acute respiratory distress syndrome in intensive care units" was published incorrect. We herewith publish the correct sentence:We found that about 30% of patients presented with the mild form of ALI, but that a minority of these (45.6%) did not evolve to ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
4
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(146 citation statements)
references
References 0 publications
2
130
4
10
Order By: Relevance
“…Ninety-day mortality for ARF was 31%, lying within the 31-42% reported in the literature [2][3][4][5]7]; as many as 48.4% of patients had some disability on admission. The figure of 47% mortality for ALI/ARDS falls within the expected 39-60% of epidemiological studies [4,7,10,12,13]. Once more, severity of illness on admission according to SAPS II, chronic heart disease, suspected aspiration and baseline PaO 2 /FIO 2 were independently associated with a worse outcome.…”
supporting
confidence: 64%
“…Ninety-day mortality for ARF was 31%, lying within the 31-42% reported in the literature [2][3][4][5]7]; as many as 48.4% of patients had some disability on admission. The figure of 47% mortality for ALI/ARDS falls within the expected 39-60% of epidemiological studies [4,7,10,12,13]. Once more, severity of illness on admission according to SAPS II, chronic heart disease, suspected aspiration and baseline PaO 2 /FIO 2 were independently associated with a worse outcome.…”
supporting
confidence: 64%
“…By definition, ARDS patients have severe pulmonary edema in the region of 15 to 20 ml.kg -1 of body weight [7,8] and it is probable that other factors, extrapulmonary, will have a more marked prognostic impact. It should therefore be remembered that the degree of hypoxemia is a controversial prognostic factor during ARDS [9,10].…”
Section: The Consequences Of Pulmonary Edema During Ardsmentioning
confidence: 99%
“…In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].Although the overall survival rate is improving [9,10], there is a notable difference when considering in-hospital mortality over several observational studies [2][3][4][8][9][10][11]. This may be explained by differences in risk factors, availability of diagnostics, ability to recognise ARDS and some selection biases affecting clinical trials [12].…”
mentioning
confidence: 99%